An atypical case of infective endocarditis initially diagnosed as myopericarditis - Negin Ceraolo; Rachel Dietz; Spencer Prete; Erin L Simon (JEM Reports)
Background: Acute myopericarditis is inflammation of the pericardium, or the membrane surrounding the heart, and the myocardium, or the muscular myocardial layer of the heart. Infective endocarditis is an infection of the cardiac endothelium. Diagnosis relies on clinical evaluation, blood cultures to identify the causative organism, and echocardiography to visualize vegetations on heart valves. In the emergency department (ED), distinguishing between myopericarditis and infective endocarditis is crucial to avoid misdiagnosis. Case report: We present the case of a 36-year-old male who was initially hospitalized for myocarditis and discharged on medications with cardiology follow-up planned. Twelve days later, the patient was readmitted with recurring chest pain. A bedside cardiac ultrasound showed mild mitral regurgitation. The patient was found to have bacteremia with Streptococcus anginosus which was concerning for endocarditis. The patient was transferred to a quaternary care hospital, where he underwent successful mitral valve repair. Why should an emergency physician be aware of this?: In the ED setting, it is crucial to broaden differential diagnoses. Myopericarditis can sometimes result from endocarditis, which can present in various ways. Therefore, endocarditis should be ruled out in acute presentations of chest pain. To avoid missing cases of endocarditis, obtaining blood cultures from patients with myopericarditis symptoms is essential. Additionally, expediting a transesophageal echocardiogram (TEE) can lead to a faster and more accurate diagnosis. Promptly conducting these tests can reduce the number of missed endocarditis cases and prevent patients from returning to the emergency department.